2023
DOI: 10.1038/s42004-023-00836-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic screening of gas diffusion layers for high performance CO2 electrolysis

Abstract: Certain industrially relevant performance metrics of CO2 electrolyzers have already been approached in recent years. The energy efficiency of CO2 electrolyzers, however, is yet to be improved, and the reasons behind performance fading must be uncovered. The performance of the electrolyzer cells is strongly affected by their components, among which the gas diffusion electrode is one of the most critical elements. To understand which parameters of the gas diffusion layers (GDLs) affect the cell performance the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 42 publications
2
38
1
Order By: Relevance
“…[57] Furthermore, also in a recent study for CO 2 -to-CO no significant effect of the hydrophobic treatment of the GDL on the selectivity of the electroreduction was observed in the absence of an MPL. [37] Both is the opposite of the present findings. However, the disagreement may be explained by the different use cases.…”
Section: Effect Of the Hydrophobic Treatmentcontrasting
confidence: 99%
See 2 more Smart Citations
“…[57] Furthermore, also in a recent study for CO 2 -to-CO no significant effect of the hydrophobic treatment of the GDL on the selectivity of the electroreduction was observed in the absence of an MPL. [37] Both is the opposite of the present findings. However, the disagreement may be explained by the different use cases.…”
Section: Effect Of the Hydrophobic Treatmentcontrasting
confidence: 99%
“…Only during long-term measurements (> 100 h), GDEs based on thicker GDLs had an advantage over thinner ones. [37] A possible reason for this was given in a study for CO 2 -to-formate, where thicker GDLs, driven by custom-made MPLs with increasing thickness, showed better performance than thinner ones, due to the extended prevention of pore flooding. [58] On the contrary, it has also been reported that an increased GDL thickness may affect the GDE performance negatively, due to decreased transport rates of CO 2 .…”
Section: Effect Of the Gdl Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…A fully ooded micro-porous layer (MPL) poses a considerable barrier of around 20-40 µm between the coordinate of dissolution and the reactive surface, as the alkaline electrolyte will start buffering the reactant before it reaches the catalyst. 19 To illustrate the effect of a ooded MPL, we employed a simple reaction-diffusion model at steady-state for both architectures. Solving the model for current densities of 300 mA cm -2 along the gas-liquid phaseboundary, we see that the concentration of dissolved CO 2 is severely hampered in the ooded carbon MPL case compared to an ePTFE electrode (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1c). As catalyst layer thicknesses (0.1 to 5 µm) are much thinner than carbon-GDE's (200 to 500 µm), 19 current distribution through the catalyst layer results in much higher in-plane ohmic resistances than in carbon-GDE's, which deter the industrial scalability of electrolyzers with ePTFE GDE's. Even for a 5 cm 2 electrode area, the increased in-plane resistance to electron-conduction would cause a large current density disparity and affect the product selectivity of CO2RR.…”
mentioning
confidence: 99%